Towards e-science: scientific communication on the verge of paradigm change - Vrana, Radovan (Array, 2010)
Information and communication technology (ICT) has a great influence on scientific communication and work of scientists. Globally, scientists are experiencing changes in ways in which they create, find, share, process, store and use scientific information. They communicate in electronic environment with their colleagues, publish their works in electronic journals and store them in digital repositories and create virtual scientific communities. However, all aspects of scientific communication on the Internet are still not known, and require additional research. This paper offers an insight into number of aspects of communication between scientists at the Faculty of Social Science and Humanities in Zagreb.